China-ASEAN cooperation Mechanism and strategies for universal health coverage - Yikai FENG; Junyi SHI; Zhuo LI; Fujian LI; Kun ZHAI; Yinzi JIN (Editorial Office of Chinese Journal of Public Health, 2024)
The Association of Southeast Asian Nations (ASEAN) is one of the regions where China has the closest exchanges and cooperation with foreign countries. Universal health coverage （UHC）is an important pillar for achieving the health-related targets of the United Nations Sustainable Development Goals, and it is also a strategic focus of common concern for China and ASEAN. How to implement cooperation with ASEAN on UHC and enhance China's participation in regional health governance is an urgent task for deepening the China-ASEAN strategic partnership. This article summarizes the development opportunities and challenges of China-ASEAN cooperation on UHC by reviewing ASEAN policies and cooperation measures in this field. It provides strategic suggestions for China to strengthen cooperation with ASEAN on UHC in the future.